Banking crisis resolution policy - lessons from recent experience : which elements are needed for robust and efficient crisis resolution? - David G. Mayes (Center for Economic Studies and ifo Institute (CESifo), 2009)
The current financial crisis has sparked intense debate about how weak banks should be resolved. Despite international efforts to coordinate and converge on such policies, national policy advice and resolution practices differ. The resolution methods adopted in the Nordic banking crises in the 1990s are generally acknowledged to include important elements of best practice. But some of these lessons have proved hard to implement during the current crisis, and new policies have been developed as a response, particularly in the UK. Still, unresolved issues remain. These are discussed in a review of the resolution methods in the US, UK and NZ.
Keywords: G01; G21; G28; 330; crisis resolution; banks; special resolution regime; Bankenkrise; Bankenpolitik; Großbritannien; Nordeuropa; Neuseeland; USA